The British System for Anticoagulant Control - Poller, L (Thrombosis and Haemostasis, 1975)
The British system for anticoagulant control based on the use of a national reagent with a national system of reporting supported by national quality control using lyophilized plasma preparations appears to offer a model which many countries abroad seem interested in adopting to solve their own national problems. Good progress has already been made in this direction in some Commonwealth countries and in South Africa. At a symposium at the 3rd Mediterranean Congress on Thromboembolism in 1973 invited participants from all over the world agreed to set up an International Study Group to provide an international organisation for anticoagulant control, and an encouraging start has been made.